2021
DOI: 10.1108/ijoa-06-2020-2271
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of training and employee creativity on organizational innovation: a moderated mediation analysis

Abstract: Purpose The purpose of this study to understand the effects of training and creativity on organizational innovation under the moderating influence of the organizational climate. Design/methodology/approach The theoretical model is grounded in the contingent resource-based view. To test the research hypotheses, this paper has gathered the cross-sectional data using a single informant pre-tested questionnaire. The data were collected from respondents working in Indian automotive manufacturing organizations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 113 publications
0
25
0
1
Order By: Relevance
“…Abdulaal and Nordin (2020) found that creativity has a mediating role between knowledge and human resource management. Creativity also plays a significant mediating role between training and organizational innovation ( Chaubey et al, 2021 ). In addition, creativity plays a mediating role between participatory management and teacher job satisfaction ( Zavvar et al, 2021 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdulaal and Nordin (2020) found that creativity has a mediating role between knowledge and human resource management. Creativity also plays a significant mediating role between training and organizational innovation ( Chaubey et al, 2021 ). In addition, creativity plays a mediating role between participatory management and teacher job satisfaction ( Zavvar et al, 2021 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Previous studies on entrepreneurial intentions have reported a mediating role of creativity (Imran et al, 2018;Danish et al, 2019;Chaubey et al, 2021). Murad et al (2021) found that creativity significantly and positively impacts entrepreneurial intentions.…”
Section: Introductionmentioning
confidence: 95%
“…Drawing from job demand resource theory (Bakker & Demerouti, 2007;Demerouti et al, 2001) and the essential role of innovation (Areed et al, 2021;Chaubey et al, 2022;Colclough et al, 2019), the present study is crucial in grasping dynamic scenarios and providing proper examination in explaining employee's innovation capability based on types of knowledge as drivers of creativity.…”
Section: Rq3 Does Time Sufficiency Moderate the Effect Of Creativity ...mentioning
confidence: 99%
“…First, creativity and innovation are fascinating issues in recent literature (Jin & Shao, 2022;Tsouri et al, 2021;Zhao et al, 2020) because managing and improving innovation capability is increasingly crucial in the knowledge-based economy era (Bhatti et al, 2020;Chaubey et al, 2022;Ferreira et al, 2020). Creativity and innovation play an essential role in organizational sustainability by building a strong culture and climate (Aboramadan et al, 2020;Dabic et al, 2019) and a dynamic capability for competitive advantage (Ferreira et al, 2020;Mady et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Dengan demikian pelatihan akan meningkatkan pengetahuan dan kemampuan yang berhubungan dengan pekerjaan karyawan. Studi sebelumnya menunjukkan bahwa pelatihan yang efektif dapat menghasilkan kepuasan dan produktivitas kerja yang lebih tinggi, peningkatan kualitas kerja, peningkatan motivasi dan komitmen, semangat kerja dan kerja tim yang tinggi serta kreativitas karyawan (Chaubey et al, 2022;Hanaysha & Tahir, 2016). Secara tegas beberapa penelitian memberikan keterangan bahwa pelatihan dapat berkontribusi secara positif dan signifikan dalam peningkatan kinerja karyawan (Mihardjo et al, 2020;Mira & Odeh, 2019;Sendawula et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified